Prevalence of short stature, underweight, overweight, and obesity among school children in Jordan - Ayman A. Zayed; Abdallah M. Beano; Faris I. Haddadin; Sohab S. Radwan; Suhaib A. Allauzy; Motasem M. Alkhayyat; Zaid A. Al-Dahabrah; Yanal G. Al-Hasan; Al-Motassem F. Yousef (BMC, 2016)
Abstract Background The prevalence of short stature (SS) and underweight in Jordan on a national level is unknown. This study aimed to investigate, on a national level, the prevalence of short stature (SS), underweight, overweight, and obesity among school aged children in Jordan. Methods This cross-sectional study was conducted from May 2015 to January 2016 and included 2702 subjects aged 6-17 years. Jordan was classified into 3 regions; North, Center (urban), and South (rural). Public and private schools were randomly selected from a random sample of cities from each region. The socioeconomic status of the sampling locations was assessed using several indicators including education, income, healthcare and housing conditions. For each participating subject, anthropometrics were obtained. SS, underweight, overweight and obesity were defined using Center of Disease Control's (CDC) growth charts. Median Z-scores for each region, age and gender were calculated. Results The Central and Northern regions enjoyed higher socioeconomic status compared to rural Southern regions. The overall prevalence of SS, underweight, overweight, and obesity were 4.9 %, 5.7 %, 17.3 %, and 15.7 %, respectively. SS and underweight were most prevalent in the rural South, while obesity was highest in the Central region. Females were more likely to be overweight, while males were more likely to be obese. Private schools had higher prevalence of obesity and overweight than public ones. Conclusions Variations in height and weight among Jordanian school children might be affected by socioeconomic status.